2019
DOI: 10.1097/ijg.0000000000001194
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications of Ab Interno Gelatin Microstent

Abstract: Purpose: To report 4 previously undescribed postoperative complications in 4 cases of ab interno XEN45 Gel Stent (XEN) implantation following uncomplicated surgeries. Patients and Methods: A total of 51 consecutive XEN implantations performed between July 1, 2017 and April 30, 2018 were reviewed. All cases were performed by 7 experienced glaucoma surgeons affiliated with the William Beaumont Hospital, Department of Ophthalmology. Cases with postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Rooney et al reported several cases of postoperative complications after XEN implantation. Gabbay et al also stated that patients should be advised regarding failure rates, possible need for bleb revision and the resumption of medication use after XEN implantation 16,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Rooney et al reported several cases of postoperative complications after XEN implantation. Gabbay et al also stated that patients should be advised regarding failure rates, possible need for bleb revision and the resumption of medication use after XEN implantation 16,48 .…”
Section: Discussionmentioning
confidence: 99%
“…IOP elevation after Xen gel implantation could be due to the obstruction of the stent with iris tissue, blood, detached Descemet's membrane, lens cortical material if Xen implantation is combined with cataract surgery, steroid response and subconjunctival episcleral fibrosis . The Xen occlusion commonly occurs during the early postoperative weeks and Nd:Yag laser may be employed to reopen the stent.…”
mentioning
confidence: 99%
“…It is well known and expected to have numerical hypotony after XEN implantation in the early postoperative days. There have been cases of numerical hypotony following XEN reported in the literature [43,44]. In most cases, this hypotony is transient and self-resolving, but occasionally it becomes clinical hypotony.…”
Section: Clinical Hypotonymentioning
confidence: 99%
“…However, a viscoelastic with a high molecular weight (cohesive) is not recommended as it has been shown to create IOP spikes [43]. In cases of over-filtration with prominent blebs present, reports have also been published of successful management with a modified transconjunctival bleb compression suture technique and a bleb revision [44].…”
Section: Management Recommendationsmentioning
confidence: 99%